Immigrants’ Inclusion in the Workplace in Romania. The Impact of Covid-19 - Alexe, Aurica Iris (HAPSc Policy Briefs Series, 2021)
Immigration is a recent phenomenon for Romania which remains a net emigration country. The country is slowly transforming from a transit to a destination becoming more attractive for labour immigrants and immigrants for study purposes. Considering the need for evidence based policies, this paper provides an overview on the dynamic of the labour immigration in Romania and the profile and characteristics of the immigrant workers in terms of numbers, economic sectors and occupations and how and what are the mechanisms that ensure immigrants’ inclusion in the workplace in Romania. Moreover, the policy brief aims to analyse the impact that the pandemic of Covid-19 had on immigrant workers in Romania and what were the effects at macro and individual level, respectively labour immigration and immigrant workers’ access and participation on the national labour market.